Descriptive Analysis of Student Engagement in Digital-Mediated English Language Classrooms - Engelina Salainti; Alan Hubert Frederick Sanger (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The rapid integration of digital technology, especially in education, has provided a changing landscape in English language learning, leading to the importance of student engagement for success in learning. The purpose of this study is to analyze the levels and dimensions of engagement of EFL students from different majors in digitally mediated general English classes at the university level. A descriptive quantitative approach and a structured questionnaire instrument were used to measure emotional, cognitive, and technological behavioral engagement on a 1- 5-point Likert scale. Descriptive statistics, including mean, level of perceptions, and presentation distribution, were used to analyze the data. The results showed that the students were at a high level of emotional engagement (3.88) and cognitive engagement (3.78), and behavioral engagement (3.17) was at a moderate level. The findings suggest that students are generally engaged in digitally mediated English classes, but behavioral engagement remains a challenge. It is concluded that enhancing supportive and interactive elements can improve behavioral, as well as language learning outcomes.